2007
DOI: 10.1063/1.2825285
|View full text |Cite
|
Sign up to set email alerts
|

Bright upconversion white light emission in transparent glass ceramic embedding Tm3+∕Er3+∕Yb3+:β-YF3 nanocrystals

Abstract: Intense red (Er3+:F9∕24→I15∕24, Tm3+:G41→F43), green (Er3+:H11∕22, S3∕24→I15∕24), and blue (Tm3+:D21→F43, G41→H63) upconversion emissions were simultaneously generated in the transparent glass ceramics containing Tm3+∕Er3+∕Yb3+:β-YF3 nanocrystals under single 976nm laser excitation. It was demonstrated that Tm3+ behaves as the sensitizer for red luminescence of Er3+ and Er3+ as the quenching center for blue, red, and near-infrared upconversion emissions of Tm3+. Various colors of the luminescence, including pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
94
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(95 citation statements)
references
References 29 publications
1
94
0
Order By: Relevance
“…[1]. One of the possible ways for generating white light is the energy transfer upconversion (UC) process in which low energy near infrared radiation is converted to higher energies such as visible or UV radiation.…”
Section: Introductionmentioning
confidence: 99%
“…[1]. One of the possible ways for generating white light is the energy transfer upconversion (UC) process in which low energy near infrared radiation is converted to higher energies such as visible or UV radiation.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the efficiency of a white UCL depends on the concentrations of Ln 3+ ions [35]. Here, for the first time, a white UCL is obtained through the double doping of Ln 3+ ions into the ZnO SNCs.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we showed that the reaction time and temperature, the size of the samples, and the concentration of the doping ions affect the UCL properties of Yb/Tm/ZnO nanoparticles [30][31][32][33][34][35][36]. In order to analyze the functional dependence of the morphology, three sets of samples were prepared with different concentrations of OH .…”
Section: Synthesismentioning
confidence: 99%
“…Park et al 97 reported bright green emission in (Ba 1 572 nm. 106 White light was also simulated by RGB color mixing in TmErYb, 107 TmHoYb, 108 PrErYb (Fig. 4).…”
mentioning
confidence: 99%